PERBANDINGAN MOTIVASI BELAJAR MAHASISWA YANG MENGIKUTI PEMBELAJARAN DARING DAN TATAP MUKA DI PENDIDIKAN BIOLOGI UNIVERSITAS COKROAMINOTO PALOPO. - Fitrah Al Anshori; Nur Muhajirah Yunus (Jurnal Biogenerasi, 2022)
The purpose of this study is to find out which is the higher learning motivation of students who participate in learning boldly and to find out the motivation of students to learn offline. The research method used in this research is the questionnaire method. The questionnaire contains questions about student motivation to take part in learning on campus with a hybrid system. Based on the analysis of the questionnaire data obtained, it can be said that the highest student motivation in the learning process is in an attractive condition. Students need direct interaction with friends and with lecturers in the classroom.